Social, cultural, and behavioral modeling : 9th International Conference, SBP-BRiMS 2016, Washington, DC, USA, June 28-July 1, 2016, Proceedings /: 9th International Conference, SBP-BRiMS 2016, Washington, DC, USA, June 28-July 1, 2016, Proceedings. (2016) - Unknown
No abstract available